Unexpected decrease of full-length prion protein in macaques inoculated with prion-contaminated blood products - Jaffré, Nina; Delmotte, Jérôme; Mikol, Jacqueline; Deslys, Jean-Philippe; Comoy, Emmanuel (Frontiers in Molecular Biosciences, 2023)
The presence of prion infectivity in the blood of patients affected by variant Creutzfeldt–Jakob disease (v-CJD), the human prion disease linked to the bovine spongiform encephalopathy (BSE), poses the risk of inter-human transmission of this fatal prion disease through transfusion. In the frame of various experiments, we have previously described that several cynomolgus macaques experimentally exposed to prion-contaminated blood products developed c-BSE/v-CJD, but the vast majority of them developed an unexpected, fatal disease phenotype focused on spinal cord involvement, which does not fulfill the classical diagnostic criteria of v-CJD. Here, we show that extensive analyses with current conventional techniques failed to detect any accumulation of abnormal prion protein (PrPv−CJD) in the CNS of these myelopathic animals, i.e., the biomarker considered responsible for neuronal death and subsequent clinical signs in prion diseases. Conversely, in the spinal cord of these myelopathic primates, we observed an alteration of their physiological cellular PrP pattern: PrP was not detectable under its full-length classical expression but mainly under its physiological terminal-truncated C1 fragment. This observed disappearance of the N-terminal fragment of cellular PrP at the level of the lesions may provide the first experimental evidence of a link between loss of function of the cellular prion protein and disease onset. This original prion-induced myelopathic syndrome suggests an unexpected wide extension in the field of prion diseases that is so far limited to pathologies associated with abnormal changes of the cellular PrP to highly structured conformations.